Determinant Of Student Intention To Take Certified Accurate Professional - Muflihah, Fikrotul; Kholilah, Kholilah (Universitas Gorontalo, 2024)
This study aims to determine the controlling attitude, motivation, interest, and perception of accounting students in their decision to take the Certified Accurate Professional. This research uses Maslow's theory of motivation. This study used quantitative research methods. Data analysis in this study used Partial Least Square (PLS). The results showed that control attitude variables and interest variables positively affected the decision of accounting students to take CAP accounting certification. It described that accounting students of UIN Malang Class of 2020 have a high attitude of control and interest in taking CAP accounting certification. Motivation and perception variables do not affect the decision of accounting students in the class of 2020 to take CAP accounting certification. It explained the need for more motivation and perception from UIN Malang Class of 2020 accounting students regarding the positive impact and some things obtained when someone chooses to take CAP accounting certification.